Evaluation of the performance of crowdfunding sharinghappiness.org in mobilizing the active role of the community to achieve SDGS 1.1 - Lubis, Ratna Lindawati; Sahidan, Sahidan (International Journal of Accounting and Management Information Systems, 2024)
Purpose: This study aims to evaluate the effectiveness of SharingHappiness.org, a crowdfunding platform in Indonesia, in mobilizing community participation to support the achievement of SDG 1.1, which focuses on eradicating extreme poverty. Research methodology: The research employs a qualitative approach using in-depth interviews with five key stakeholders (platform managers, donors, and campaigners), supported by thematic analysis and triangulation. Questionnaires were also distributed to 57 donors and campaigners to strengthen the analysis through mixed data validation. Results: Findings reveal that donor trust, ease of transaction, transparency, influencer influence, brand awareness, and inclusivity are critical success factors. While SharingHappiness.org has shown commendable performance in these areas, it still lags behind larger platforms such as Kitabisa.com in terms of donation volume, donor base, and campaign success rate. However, SharingHappiness.org demonstrates higher operational efficiency per employee. Conclusions: The study concludes that strengthening transparency, improving UI/UX, expanding strategic partnerships, and enhancing long-term impact reporting are essential to increasing community participation and aligning better with SDG 1.1 goals. Limitations: The study is limited by its qualitative scope and focus on a single platform, which may reduce generalizability to other crowdfunding contexts. The quantitative comparison with competitors is based on publicly available data, which may lack full accuracy. Contribution: This research contributes to the literature on digital philanthropy and SDG implementation in developing countries by providing an evaluative framework for assessing crowdfunding effectiveness in promoting social inclusion and poverty alleviation.